PERBANDINGAN KINERJA KARYAWAN SEBELUM DAN SESUDAH PEMBERIAN PENDIDIKAN DAN PELATIHAN PADA PT. ASURANSI INTRA ASIA CABANG MEDAN - Manullang, Ida M. (UNIKA Santo Thomas, 2018)
This study aims to analyze the comparison of employee performance before and after the provision of education and job training at PT. Intra Asia Insurance Medan Branch. Data collection by interviews and documentation. The population is all employees of the company and the sample in this study uses saturated samples, namely sampling to all agents totaling 35 people. Data analysis techniques with different test two average paired samples. The results of the study resulted in a level of difference before and after the provision of education and job training showed a z_count value of 24.23> 1.96 which means that there were significant differences between the performance of employees after and received training before getting training. From the results of hypothesis testing, the formulation of the hypothesis proposed for validity test shows that there are significant differences in employee performance before and after the provision of education and job training. Thus, the hypothesis proposed in this study can be accepted.Suggestions given, the company should provide education and training regularly, especially for employees with performance that does not meet the standards and providing education and training for employees who have met the standards also need to be done in an effort to increase the policy targets set by the company.